Anatomy of symbiotic fungal endophytes in Psilotum nudum (L.) P. Beauv - Affina E.; Noraini Talip; Nazlina Ibrahim (Malaysian Society of Applied Biology, 2015)
A study was undertaken to identify the presence of fungal endophyte in fern plant, Psilotum nudum. Being the only living species of a once populated division, P. nudum is the most primitive vascular plant. Cross section of stipe and rhizoid parts was done to observe the presence of endophyte within parenchyma cells. Samples of P. nudum were collected at different sites in Bangi. Anatomical study showed P. nudum has percentage of infected cells highest in rhizoid parenchyma cortex (22.2%) and lowest in the apical area (3.1%). Eleven fungal endophyte isolates were successfully isolated and identified from P. nudum with Aspergillus being the major genus. Is Aspergillus a host-specific endophyte? The present study shows the compatibility of P. nudum parenchyma cells as a host to fungal endophyte.